Economy, state and values: Relevance of some neglected Indian ideas in the emerging scenario - Banerji, Pranab (1994)
"In the emerging context of market-oriented development, visualising lesser state intervention, the author raises the issue of relevance of traditional humanistic and ethical values to disprove their antagonism with development as they help creation of better human beings with better life as a by-product"
Keywords: Development planning - India; India - Economic policy; Public administration - India; Public administration